Analisa Penerapan E-Filling Dalam Meningkatkan Kepatuhan Pelaporan SPT Tahunan Wajib Pajak Orang Pribadi di KPP Pratama Rantau Prapat - Indri Apriani; Arnida Wahyuni Lubis (VISA: Journal of Vision and Ideas, 2022)
Tax is a levy that must be given to the state by individual or entities based on the law that will be used for the benefit of the state.individuals or taxpayers must report their income or income, namely by repoting the annual SPT this useful for fulfilling the obligation to pay taxes.in two ways,namely manually and online. manually using form 1770 and online using the E-Filling apllication. The purpose of this study was to determine the role of E-Filling in increasing compliance with reporting individual taxpayers' annual tax returns.this research is included in the type of descriptive research with a qualitative approach. the results of this study indicate that the presence of E-Filling is able to increase taxpayer compliance in annual SPT reporting is due to the practice of using it can be done anywhere and anytime. Keywords: E-Filling, individual taxpayers'